1994
DOI: 10.1083/jcb.125.1.215
|View full text |Cite
|
Sign up to set email alerts
|

Residues within a conserved amino acid motif of domains 1 and 4 of VCAM-1 are required for binding to VLA-4.

Abstract: Abstract. Vascular cell adhesion molecule 1 (VCAM-1), a member of the Ig superfamily originally identified on activated endothelium, binds to the integrin very late antigen-4 (VLA-4), also known as ot4~l or CD49d/CD29, to support cell-cell adhesion. Studies based on cell adhesion to two alternatively spliced forms of VCAM-1 or to chimeric molecules generated from them and intercellular adhesion molecule-1 (ICAM-1) have demonstrated two VLA-4 binding sites on the predominate form of VCAM-1. Here, we studied VLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(75 citation statements)
references
References 62 publications
2
73
0
Order By: Relevance
“…From two experiments, the EC 50 range of cell adhesion for 7D VCAM-1(Ig) was 50 -56 ϫ 10 Ϫ12 M, and the EC 50 of cell adhesion for 6D VCAM-1(Ig) was 50 -62 ϫ 10 Ϫ12 M. Equal capture of VCAM-1 was confirmed by ELISA with biotinylated VCAM-1 mAb 1.4C3 (Fig. 3, dotted line), which recognizes an epitope within domain 2 of VCAM-1 in both 7D and 6D VCAM-1 (27). No significant adhesion was seen to control wells coated with BSA (data not shown).…”
Section: Increased Strength Of Adhesion To 7d Vcam-1 Under Conditionsmentioning
confidence: 97%
See 4 more Smart Citations
“…From two experiments, the EC 50 range of cell adhesion for 7D VCAM-1(Ig) was 50 -56 ϫ 10 Ϫ12 M, and the EC 50 of cell adhesion for 6D VCAM-1(Ig) was 50 -62 ϫ 10 Ϫ12 M. Equal capture of VCAM-1 was confirmed by ELISA with biotinylated VCAM-1 mAb 1.4C3 (Fig. 3, dotted line), which recognizes an epitope within domain 2 of VCAM-1 in both 7D and 6D VCAM-1 (27). No significant adhesion was seen to control wells coated with BSA (data not shown).…”
Section: Increased Strength Of Adhesion To 7d Vcam-1 Under Conditionsmentioning
confidence: 97%
“…Also, removal of Ig-like domains COOH-terminal to domain 3 or simply substituting Asp 328 with Ala increases the relative affinity of 7D VCAM-1 for ␣ 4 ␤ 1 . Previous functional and structural studies of the two NH 2 -terminal domains of VCAM-1 (domains 1 and 2) have demonstrated that the primary ␣ 4 ␤ 1 binding site in domain 1 resides in a solvent-exposed loop (the C-D loop, which contains the essential residue Asp 40 ) (25,27,29,40,41). A secondary "synergy" site, the CЈ-E loop-E strand, is located in the upper face of domain 2 (30), spatially close to the C-D loop of domain 1 (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations